Destinação e utilização de resíduos industriais siderúrgicos em outras indústrias: estudo de casos - Murakami, Fabio Kazuhiro (Universidade do Vale do Rio dos Sinos, 2014)
The industrial waste management becomes a strategic issue in business. The increase of environmental awareness by consumers and the legal requirements has led companies to review their position regarding face the disposal of their industrial waste. A competitive analysis of supply chains can not be restricted to the traditional one-way flow of products. The reverse channel of wastes should also be evaluated, aiming to close the cycle for the reuse of materials or the use of industrial waste in other applications. In this context, the steel industry distinguished by its ability to use scrap metal as raw materials and generate industrial wastes capable of being used as raw material in other industrial sector. The objective of this study is to analyze the potential to establish an environmentally sustainable supply-chain through the reuse of industrial waste arising in the steel industry. To accomplish this, two case studies were conducted. In the first study was reported the relations between seven companies belonging to the same supply chain and discussed how these relations can help to break down barriers and encourage the reuse of waste. In the second case study were assessed four main waste generated by a steel mill, evaluating the possibilities and limits for the reuse of the waste as raw material in other economic activities. The results showed that most relationships order to reuse the waste is strictly commercial. The reuse increases when the companies levels’ of dependency for the waste is higher. Even with a high degree of dependence, external factors may prevent the use of waste. Extrapolate the business relation of the companies for a collaborative relationship can help to mitigate these external factors, break down the barriers and increase the reuse of waste. Cost prevents the installation of new industrial operations to only the use of industrial waste as raw material. However there are opportunities for the installation of companies or cooperatives able to rework the steel waste for use in other applications.
Keywords: Resíduos industriais; Cadeia de suprimentos; Relacionamento; Indústria siderúrgica; Simbiose industrial; Industrial wastes; Supply-chains; Relationships; Steel industry; Industrial symbiosis; ACCNPQ::Engenharias::Engenharia de Produção